Pengaruh pelatihan penggunaan tensimeter digital terhadap keterampilan penggunaan tensimeter digital pada kader posyandu - Arin Proborini, Christiana; Rahmayanti, Yeni Nur; Arifa, Ima (JURNAL KESEHATAN PRIMER, 2023)
Introduction: One of the Posyandu services for the elderly is blood pressure measurement, but the tool used is an analog tensimeter and how it works is still done manually. Posyandu cadres who are currently running are used to using these tools, but with the addition of a digital tensimeter, training is needed again on how to use a digital tensimeter. The purpose of this study was to determine the effect of training on the use of a digital tensimeter on the skills of using a digital tensimeter for Posyandu cadres. Methods: This research method used quantitative with a quasi-experimental design with a one group pre-test and post-test approach with 24 cadres as respondents. Data collection was carried out before and after training using standard operating procedures. Results: Data analysis using statistical tests using the Wilxocon test showed that the results of this study obtained a significance value of 0.000 so that <0.05 indicated that there was a significant effect between training on the use of a digital tensimeter on the skills of posyandu cadres. Conclusion:  Training on the use of digital blood pressure meters is effective in increasing the skills of cadres in using digital blood pressure meters. Therefore, training targeting all Posyandu cadres can be used as a strategy to improve skills in using digital blood pressure meters and the accuracy of measuring blood pressure, reminding that digital blood pressure meters are a new tool.